Analysis of Work Posture on Employees of the RHI Department of PT. Cikampek Kujang Fertilizer Using the RULA Method - Septianto, Farras; Fasa, Nadia (UNISTEK, 2023)
PT. Pupuk Kujang Cikampek is a producer of urea fertilizer, as well as marketing its own products and other products to customers, namely food farmers, smallholder plantations and smallholder fisheries as a Public Service Obligation (PSO) obligation for subsidized fertilizers and other customers for non-subsidized. The problem faced is regarding inappropriate work postures, causing complaints to employees because some work is done manually with postures that are not in accordance with ergonomic rules. This study aims to identify work postures carried out by employees using the Rapid Upper Limb Assessment (RULA) method. The results of this study indicate that the 3 employees who were analyzed using the RULA method were obtained for employees in the payroll and HR management unit producing a final score of 7, which means that work attitudes are considered dangerous, then for employees in the industrial relations unit, they produce a final score of 4, which means that work attitudes are at low risk. , and the last on employee insurance and employee welfare produces a final score of 3 which means that work attitudes include those with low risk.